2021
DOI: 10.1111/iej.13438
|View full text |Cite
|
Sign up to set email alerts
|

The restoration of root filled teeth: a review of the clinical literature

Abstract: Clinicians often face dilemmas regarding the most appropriate way to restore a tooth following root canal treatment. Whilst there is established consensus on the importance of the ferrule effect on the predictable restoration of root filled teeth, other factors, such as residual tooth volume, tooth location, number of proximal contacts, timing of the definitive restoration and the presence of cracks, have been reported to influence restoration and tooth survival. The continued evolution of dental materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 148 publications
1
65
0
Order By: Relevance
“…The clinical samples were followed up to 18 years and failures were observed mainly within the first years of clinical service. This finding showed that when root fracture was avoided by covering cusps with the crown or the direct restoration, the teeth were protected from occlusal loading [ 32 ]. Moreover, when partial or complete healing of the periapical lesion was achieved, the restored root remained in clinical service without any clinical sign or symptom.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical samples were followed up to 18 years and failures were observed mainly within the first years of clinical service. This finding showed that when root fracture was avoided by covering cusps with the crown or the direct restoration, the teeth were protected from occlusal loading [ 32 ]. Moreover, when partial or complete healing of the periapical lesion was achieved, the restored root remained in clinical service without any clinical sign or symptom.…”
Section: Discussionmentioning
confidence: 99%
“…To restore fracture resistance in teeth, modern dentistry has shifted towards bonded restorative procedures. [13][14][15][16] Since the modulus of elasticity of composite resin is close to that of dentin, restoring endodontic cavities with composite resin showed a minimal stress jump at the resin-dentin interface, reduced cuspal flexure, and lowered probability of coronal fracture as suggested by Soares PV (2008), Taha NA (2014) [13,[18][19][20] . Therefore, in the present study restoration of PCD was done by dentin bonded composite and its impacts on microstrain distribution and load to failure was studied.…”
Section: Discussionmentioning
confidence: 99%
“…The patient inclusion criteria were as follows: No self-reported systemic diseases present At least one tooth with AP (necrotic pulp and/or filled root canals with radiographically determined signs of post-treatment endodontic disease requiring root canal retreatment) Absence of clinical periodontal inflammation on the tooth indicated for treatment, either anatomically intact or, with the reduced periodontium [ 18 ] Baseline CBCT images available prior to the study (images taken for general oral rehabilitation planning purposes no earlier than 1 month prior to endodontic procedures). …”
Section: Methodsmentioning
confidence: 99%
“…Absence of clinical periodontal inflammation on the tooth indicated for treatment, either anatomically intact or, with the reduced periodontium [ 18 ]…”
Section: Methodsmentioning
confidence: 99%